2020
DOI: 10.1002/jdd.12045
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of virtual patients in teaching clinical decision‐making skills to dental students

Abstract: Objectives The aim of this study was to investigate the effect of virtual patient‐based training on the clinical decision‐making ability of dental students. Methods This quasi‐experimental study with pretest and posttest design was conducted on 76 (2015 admitted) dental students of Shiraz Dental School in 2018–2019. The study samples were randomly divided into 2 groups: intervention (web‐based virtual patient training = 36) and control (face‐to‐face case‐based training, n = 40). The data collection tools in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
1
14
0
5
Order By: Relevance
“…Despite the fact that few studies reported longer periods of follow-up and reported insignificant differences between virtual and traditional groups. 39,48,49,74 The diversity in students' learning styles and motivation is the crucial challenge which course designers face. The introduction of virtual simulators in the dental curriculum and the utilization of its data to stratify dental students and predict their clinical performance would provide the opportunity to tailor the learning process to meet individual diversity in students' expertise and allow students to work at their own pace.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that few studies reported longer periods of follow-up and reported insignificant differences between virtual and traditional groups. 39,48,49,74 The diversity in students' learning styles and motivation is the crucial challenge which course designers face. The introduction of virtual simulators in the dental curriculum and the utilization of its data to stratify dental students and predict their clinical performance would provide the opportunity to tailor the learning process to meet individual diversity in students' expertise and allow students to work at their own pace.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a web-based VP training study on herpes simplex infection and recurrent aphthous stomatitis found an improved learning in dental students. 25 The learning platforms can also offer the possibility of case-based discussions. Besides chat discussion, live discussions are allowed, as well as sharing clinical, imaging and/or histopathological images.…”
Section: Preclinical and Clinical E-learning Activities During The Covid-19 Eramentioning
confidence: 99%
“…First, e-learning is a reality in many DSs, with an increasing popularity in the last few years (41,44,48,38). Second, the alumni accepted e-learning strategies as part of their curricula, and many reports identified several benefits after its implementation (27,28,30,(32)(33)(34)(35)(36)(37)(39)(40)(41)(42)(43)(45)(46)(47)(52)(53)(54)(55)(56)(57). Third, e-learning represents a point of debate within academics since some disciplines consider its application as valuable as the traditional teaching methods, while others considered it only as a good complement (29,42,44,50,53,58).…”
Section: Maresca C Etal 2014 (58)mentioning
confidence: 99%